Nothing Ventured - Nothing Gained? Empirical Evidence on Venture Capital Financing in Switzerland - Christian Hopp (Swiss Journal of Economics and Statistics, 2007)
This paper analyses the Determinants of Venture Capital Staging and Syndication in Switzerland. I find that among the different affiliations of VC investors in Switzerland especially independent investors make more extensive use of staged capital infusions. Moreover, the results suggest that staging is employed as a tool for mitigating risks in VC financing. In addition, I find that Syndication can serve as an entrance strategy for foreign VC providers. Furthermore, I find evidence that firms, which realize the benefit of staging, do also become conscious of the value added in financing Start Ups by involving partners. Consequently, VC firms that make use of staging are also more open to syndication. With respect to the value-added of Co-Investment behavior, I show that syndication positively impacts the success rate of a VC provider, whereas VC firms that are more locally embedded do exhibit lower success rates for their investment portfolio.
Keywords: G24; G31; 330; Venture Capital; Entrepreneurship; Syndication